2017
DOI: 10.1039/c6ra24404a
|View full text |Cite
|
Sign up to set email alerts
|

Protein–inorganic hybrid system for efficient his-tagged enzymes immobilization and its application in l-xylulose production

Abstract: Efficient his-tagged recombinant enzyme nanoflowers were synthesized and used for rare sugar production under co-factor regeneration conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…There is a wide range of enzyme immobilization techniques involving physical entrapment or chemical interactions (either covalent or non-covalent) between the enzyme and the support [9,[12][13][14][15][16]. These techniques have been applied to many enzymes, including -galactosidases [5,9,12,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide range of enzyme immobilization techniques involving physical entrapment or chemical interactions (either covalent or non-covalent) between the enzyme and the support [9,[12][13][14][15][16]. These techniques have been applied to many enzymes, including -galactosidases [5,9,12,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…EY (%) = 100 9 protein concentration of nanohybrids/ initial protein concentration (mg/mL) [11]. The immobilized enzymes were characterized by scanning electron microscopy (SEM), confocal microscopy, and energy dispersive x-ray spectroscopy (EDX).…”
mentioning
confidence: 99%
“…Their result showed that for the synthesis of enzyme hNFs, the relative activity of the obtained immobilized enzyme was greatly decreased from 246 AE 21% (24 h incubation) to 14.4 AE 2.1% (3 days incubation) for L-arabinitol 4-dehydrogenase from Hypocrea jecorina and from 144 AE 16% (24 h incubation) to 17.1 AE 12% (3 days incubation) for NADH oxidase from Streptococcus pyogenes. 15,43 Characterization of tfdB-JLU-hNFs…”
Section: Growth Of Tfdb-jlu-hnfsmentioning
confidence: 99%